Notes on Carex (Cyperaceae) from China: three new species - Zhou, Ying-Ying; Jin, Xiao-Feng (Phytotaxa, 2014)
Carex remotistachya, C. daxinensis and C. fangiana, three new species from China, are described and illustrated. Carex remotistachya resembles C. doniana (sect. Molliculae), differing by having spikes remote, staminate spikes with a 3–5 cm long peduncle at the base, leaves 3–6 mm wide, and stigmas shorter than perigynia. Carex daxinensis is similar to C. caudispicata (sect. Radicales), but differs in having perigynia ellipsoid-ovoid, 4–4.5 mm long, staminate parts of spikes shorter than pistillate ones, and leaves 2–3.5 mm wide. Carex fangiana is similar to C. nitidiutriculata (sect. Hymenochlaenae), differing by having leaves 6–9 mm wide, staminate spike solitary, and perigynia glabrous.